The commitment of Freemasonry with education at the end of the 20th century. The case of the America lodge of Ubrique (Cádiz) - Morales Benítez, Antonio (2017)
The present work analyzes the activity of the America lodge in a locality of rural Andalusia. It provided further education to those who were unable to have access to culture through diverse institutions sponsored by masonry as a means or instrument to fight the misfortunes which afflicted the population by training and educating citizens to ensure their development.